Modeling economic reform in North Korea - Noland, Marcus; Robinson, Sherman; Scatasta, Monica (Institute for International Economics, 1996)
This paper examines the possible implications of economic reform in North Korea, especially opening to trade. A computables general equilibrium (CGE) model of the North Korean economy is used to analyze a variety of trade liberalization scenarios